Clinical characteristics and treatment patterns of pregnant women with hypertension in primary care in the Federal Capital Territory of Nigeria: cross-sectional results from the hypertension treatment in Nigeria Program - Zainab Mahmoud; Ikechukwu A. Orji; Gabriel L. Shedul; Kasarachi Aluka-Omitiran; Nanna Ripiye; Blessing Akor; Helen Eze; Tunde Ojo; Guhan Iyer; Abigail S. Baldridge; Lisa R. Hirschhorn; Mark D. Huffman; et al. (BMC, 2023)
Abstract Background Hypertensive disorders of pregnancy, including hypertension, are a leading cause of maternal mortality in Nigeria. However, there is a paucity of data on pregnant women with hypertension who receive care in primary health care facilities. This study presents the results from a cross-sectional analysis of pregnant women enrolled in the Hypertension Treatment in Nigeria Program which is aimed at integrating and strengthening hypertension care in primary health care centres. Methods A descriptive analysis of the baseline results from the Hypertension Treatment in Nigeria Program was performed. Baseline blood pressures, treatment and control rates of pregnant women were analysed and compared to other adult women of reproductive age. A complete case analysis was performed, and a two-sided p value < 0.05 was considered statistically significant. Results Between January 2020 to October 2022, 5972 women of reproductive age were enrolled in the 60 primary healthcare centres participating in the Hypertension Treatment in Nigeria Program and 112 (2%) were pregnant. Overall mean age (SD) was 39.6 years (6.3). Co-morbidities were rare in both groups, and blood pressures were similar amongst pregnant and non-pregnant women (overall mean (SD) first systolic and diastolic blood pressures were 157.4 (20.6)/100.7 (13.6) mm Hg and overall mean (SD) second systolic and diastolic blood pressures were 151.7 (20.1)/98.4 (13.5) mm Hg). However, compared to non-pregnant women, pregnant women had a higher rate of newly diagnosed hypertension (65.2% versus 54.4% p = 0.02) and lower baseline walk-in treatment (32.1% versus 42.1%, p = 0.03). The control rate was numerically lower among pregnant patients (6.3% versus 10.2%, p = 0.17), but was not statistically significant. Some pregnant patients (8.3%) were on medications contraindicated in pregnancy, and none of the pregnant women were on aspirin for primary prevention of preeclampsia. Conclusions These findings indicate significant gaps in care and important areas for future studies to improve the quality of care and outcomes for pregnant women with hypertension in Nigeria, a country with the highest burden of maternal mortality globally.